Analisis Pengaruh Penambahan Eco-Enzyme Limbah Kubis Terhadap Pengawetan Buah Tomat Dengan Perbandingan Variasi Substrat - Nur Laela; Andari Puji Astuti; Endang Tri Wahyuni Maharani (Hydrogen: Jurnal Kependidikan Kimia, 2022)
Cabbage is a vegetable that thrives in Indonesia. This type of vegetable is a vegetable that is not durable and prone to decay and produces organic waste waste from cabbage leaves which causes unpleasant odors that can pollute the environment. Waste from cabbage can be used as a base for making eco-enzyme fluids. Eco-enzyme liquid is a liquid produced from the fermentation of organic waste, this liquid has a reddish brown color, has a fresh and strong odor. This eco-enzyme contains propionate acid which can inhibit microorganisms in the decay process so that it can be used as a natural preservative. The purpose of this study was to analyze the effect of adding eco-enzyme solutions on tomato fruit preservation and to find out on what day of the tomatoes decomposed and changes in tomatoes that were not sprayed with eco-enzymes. This type of research is an experimental study using 2 types of substrate variations, namely by using the basic ingredients of making eco-enzyme liquid using palm sugar with cabbage waste (Variable 1) and sugar with cabbage waste (Variable 2). Based on the research results, it was found that the eco-enzyme liquid, palm sugar substrate was 60% and granulated sugar substrate was 40% and the most effective eco-enzyme liquid for natural preservatives in tomatoes is eco-enzyme using palm sugar.